1990
DOI: 10.5962/bhl.title.3109
|View full text |Cite
|
Sign up to set email alerts
|

Variability and significance of parietal and ventral scales in the marine snakes of the genus Lapemis (Serpentes, Hydrophiidae), with comments on the occurance of spiny scales in the genus / Paul Gritis, Harold K. Voris.

Abstract: Literature Cited 11 Appendix 13 3. Ventral scale states in Lapemis 3 4. Dorsum of head of Australian Lapemis showing fragmented parietal scales 3 5. Frequency distributions of parietal scale

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…These species were diagnosed according to differences in their parietal and ventral scales (Smith ). However, Gritis & Voris () examined nearly 1400 specimens and found that these characters varied continuously across the species' collective range and as a result referred both species to L. curtus . Given that our molecular genetic analyses strongly support the presence of two largely reproductively isolated species in the IO and WP, a re‐evaluation of additional morphological traits that may separate these lineages is needed.…”
Section: Discussionmentioning
confidence: 99%
“…These species were diagnosed according to differences in their parietal and ventral scales (Smith ). However, Gritis & Voris () examined nearly 1400 specimens and found that these characters varied continuously across the species' collective range and as a result referred both species to L. curtus . Given that our molecular genetic analyses strongly support the presence of two largely reproductively isolated species in the IO and WP, a re‐evaluation of additional morphological traits that may separate these lineages is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrophis platurus is found both in the Pacific and Indian Oceans, and a few specimens have been observed in the Atlantic Ocean (Bessesen & Galbreath, 2017;Branch, 1998). Other species, such as H. caerulescens, H. cyanocinctus, H. curtus H. ornatus, H. peronii, H. spiralis, and H. stokesii have a very wide distribution in both Asia as well as in the Australian region ((Buzas et al, 2019;David & Ineich, 1999;Gritis & Voris, 1990;Ineich & Rasmussen, 1997;Rasmussen et al, 2014;Rezaie-Atagholipour et al, 2016). With their wide distribution some viviparous sea snake species have potential for use in existing monitoring programs across these regions.…”
Section: Criterion 4: Higher Taxa Widely Distributed Geographically and Over A Breadth Of Habitatmentioning
confidence: 99%
“…Remarks: One of the most frequently caught sea snakes by trawling boats in Asia. Lapemis hardwickii is a synonym of L. curtus (Gritis & Voris, 1990) Laticauda Laurenti Laticauda colubrina (Schneider): (McCarthy, 1986;Heatwole et al, 2005;Kharin, 2006).…”
Section: Lapemis Graymentioning
confidence: 99%